The tiger's wife : a novel - Obreht, Téa. (Random House, 2011)
Remembering childhood stories her grandfather once told her, young physician Natalia becomes convinced that he spent his last days searching for "the deathless man," a vagabond who claimed to be immortal. As Natalia struggles to understand why her grandfather, a deeply rational man would go on such a farfetched journey, she stumbles across a clue that leads her to the extraordinary story of the tiger's wife.